2005
DOI: 10.1093/rheumatology/kei162
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal ultrasound training in rheumatology: the Belfast experience

Abstract: This Belfast experience shows what can be achieved despite the absence of formal MSUS training. Nevertheless, the development of recognized training programmes and international standards of competency are important goals on the way to achieving more widespread acceptance of MSUS as a useful tool in everyday clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 16 publications
1
26
0
2
Order By: Relevance
“…After 6 months they had to pass a clinical assessment and a multiplechoice exam in ultrasound competency. 3 out of 60 did not pass the multiplechoice part of the assessment, and only 14 out of 60 passed the clinical part the assessmentin accordance with the method described by Taggart et al [1]. This showed one more time that direct supervision by an expert is an essential element in learning ultrasonography.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…After 6 months they had to pass a clinical assessment and a multiplechoice exam in ultrasound competency. 3 out of 60 did not pass the multiplechoice part of the assessment, and only 14 out of 60 passed the clinical part the assessmentin accordance with the method described by Taggart et al [1]. This showed one more time that direct supervision by an expert is an essential element in learning ultrasonography.…”
Section: Discussionsupporting
confidence: 57%
“…The outlier in the Achilles tendon figure explains partly the intra observer difference for the trainee in that setting. mum of 6 participants and a minimum of 50% of total time devoted to practical sessions [1]. In our education program both theoretical and practical MSUS was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have contributed to the development of essential issues, MSUS training method and competency assessment in rheumatology [24][25][26][27][28][29][30][31]. More recently, training in ultrasound-guided injections for rheumatologists among countries has been tested and results demonstrated that the percentage of rheumatologists receiving training in the field is <10% in over 70% of countries that participated in the survey [32].…”
Section: Education and Training In Msusmentioning
confidence: 99%
“…Formal or informal training from a colleague expert in MSUS, predominantly a rheumatologist or radiologist, has been widely used among rheumatologist ultrasonographers to achieve MSUS competency [29].…”
Section: Box 2 Forms Of Musculoskeletal Ultrasonography (Msus) Trainingmentioning
confidence: 99%